Boat for All: Interior Overhaul - Designing a Versatile Interior for Marine Public Transit - Fjellheim Eriksson, Gustav; Svanlund, Wilhelm (My University, 2024)
This project concerns the development of the interior passenger compartment of the Cstrider waterborne vessel currently being developed, intended for marine public transit. With an emphasis on comfort and accessibility, research has been conducted in the form of a literature review, public observations, and an explorative user study. This resulted in a multitude of suggestions for the interior layout, and a few were methodologically selected for further development. In the evaluation phase of the project, a complete 1:1 scale mock-up of the boat interior was constructed to conduct additional high-fidelity user experience studies. These studies were conducted to evaluate different concepts with consideration to different user groups. The results laid the foundation for the proposal of a layout design for an accessible, comfortable and versatile passenger compartment.
Keywords: user experience; accessibility; public transit; marine vessels; interior; layout